A new multi-scale coupling simulation of natural circulation system based on self-adaption data interaction method. (15th June 2023) - Cai, Weihua; Li, Zhiming; Cui, Jun; Zhang, Wenchao; Sun, Jianchuang
Highlights: A new multi-scale coupling simulation using self-adaption data interaction method was proposed. The updating strategy for natural circulation flow velocity in 1D user code was optimized. An optimization strategy for interactive flow velocity was proposed based on the dichotomy idea. Abstract: Multi-scale coupling simulation can obtain both system characteristics and three-dimensional flow field of complex structural components. Therefore, it is a significant method to investigate the safety on passive systems of nuclear reactor. Aiming at the problems in the existing data interaction strategy, this paper first built an adaptive threshold function based on historical interaction information, developed the updating strategy of natural circulation flow velocity, and proposed the optimization strategy for initial flow velocity. And then, it compared and analyzed the difference between fixed iteration number method and self-adaption data interaction method. The results showed that the convergence speed was increased by more than 78%. Both convergence speed and convergence ability were not affected by initial flow velocity. The study provides some constructive instructions to build multi-scale coupling simulation with high efficiency and strong robustness, and is helpful in jointly optimizing the design of system characteristics and nuclear reactor structure.